Captain Underpants and the Terrifying Return of Tippy Tinkletrousers - Book 9 - Pilkey, Dav, 1966- (New York : Scholastic, 2012)
"In this ninth epic novel, Dav Pilkey takes readers back in time to the carefree days of kindergarten, when the worst thing George and Harold had to face was NOT evil mad scientists or alien cafeteria ladies but a sixth-grade bully named Kipper Krupp, the nephew of their clueless school principal. And because George and Harold dont actually invent Captain Underpants until fourth grade, the two clever kindergartners are on their own -- using their brains to beat the bully. Hold on to your underpants-- the Captain is back!"--Amazon.com.
"Action, pranks, laffs"--Cover.
850
Accelerated Reader
Keywords: Captain Underpants (Fictitious character); Juvenile fiction; Time travel; Juvenile fiction; Kindergarten; Juvenile fiction; Bullying; Juvenile fiction; School principals; Juvenile fiction; Heroes; Juvenile fiction; Captain Underpants (Fictitious character); Fiction; Time travel; Fiction; Kindergarten; Fiction; Bullies; Fiction; Schools; Fiction; School principals; Fiction; Heroes; Fiction; Humorous stories; Bullies; Juvenile fiction; Captain Underpants (Fictitious character) -- Fiction; Time travel -- Fiction; Kindergarten -- Fiction; Bullies -- Fiction; Schools -- Fiction; School principals -- Fiction; Heroes -- Fiction; Time travel -- Juvenile fiction; Kindergarten -- Juvenile fiction; Bullies -- Juvenile fiction; Captain Underpants (Fictitious character) -- Fiction; Time travel -- Fiction; Kindergarten -- Fiction; Bullies; Fiction; Schools; Fiction; School principals -- Fiction; Heroes -- Fiction; Bullies -- Fiction; Schools -- Fiction